2020
DOI: 10.1016/j.gr.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Deep subduction of felsic rocks hosting UHP lenses in the central Saxonian Erzgebirge: Implications for UHP terrane exhumation

Abstract: Contrasting metamorphic conditions determined by chemical geothermobarometric investigations of ultrahigh-pressure (UHP) lenses surrounded by high-pressure (HP) and medium-pressure (MP) 2 felsic country rocks are an enigmatic feature of UHP terranes. One of the major questions arising is whether the UHP lenses and the country rocks are a product of different peak metamorphic conditions corresponding to different maximum depth or whether country rocks also experienced UHP conditions but equilibrated and/or re-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…by the presence of coesite or pseudomorphs after coesite (Schmädicke et al 1992;Massonne, 2001;O'Brien & Ziemann, 2008;Gose & Schmädicke, 2018). However, previous investigations of mineral inclusions in detrital garnet of the sampled catchments revealed that coesite-bearing UHP rocks occur in all studied catchments; they are not solely confined to eclogite and paragneiss lenses, but also include country-rock gneiss which re-equilibrated during high-temperature (HT) exhumation at HP conditions (Schönig et al 2019(Schönig et al , 2020. All lithologies occurring in the six catchments therefore represent a potential source for coesitebearing garnet grains and can be roughly subdivided into mafic sources, that is, eclogite and felsic sources (i.e.…”
Section: Geological Framework and Sampling Locationsmentioning
confidence: 90%
See 4 more Smart Citations
“…by the presence of coesite or pseudomorphs after coesite (Schmädicke et al 1992;Massonne, 2001;O'Brien & Ziemann, 2008;Gose & Schmädicke, 2018). However, previous investigations of mineral inclusions in detrital garnet of the sampled catchments revealed that coesite-bearing UHP rocks occur in all studied catchments; they are not solely confined to eclogite and paragneiss lenses, but also include country-rock gneiss which re-equilibrated during high-temperature (HT) exhumation at HP conditions (Schönig et al 2019(Schönig et al , 2020. All lithologies occurring in the six catchments therefore represent a potential source for coesitebearing garnet grains and can be roughly subdivided into mafic sources, that is, eclogite and felsic sources (i.e.…”
Section: Geological Framework and Sampling Locationsmentioning
confidence: 90%
“…Measurement conditions include an accelerating voltage of 15 kV and a beam current of 20 nA. Counting times were 15 s for Si, Mg, Ca, Fe and Al, and 30 s for Compared with the map of Schönig et al (2019Schönig et al ( , 2020, an eclogite lens was added in the catchment of sample JS-Erz-8s according to Kossmat & Reinisch (1931).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations